Lost in Translation:: The English Versions of Gabrielle Roy’s Early Novels - Kelly, Darlene (Studies in Canadian Literature / Études en littérature canadienne, 2005)
In translating the early works of Gabrielle Roy, Harry Binsse sought to make his English words "sing the same song" as the French source texts according to three principles: no omissions, no additions, no disfiguring flatness. Yet Binsse's very fidelity to these strictures led to substantive errors in the translations, altering characterization and meaning in Roy's novels. In avoiding flatness, Binsse's excessive lyricism and antiquated diction eclipsed Roy's signature simplicity. Conversely, his concern with linguistic and factual precision tended to mar any intended ambiguity or generalizations in the original text. Most significantly, Binsse's description of aboriginal and Third World peoples represents a different ideological perspective than Roy's, which the reader could mistakenly attribute to Roy. However, Binsse does ultimately adhere to his overall goal "not to build barriers" in translation, having widely contributed to the English accessibility and success of Roy's novels.